MATERIALISTIC CULTURE IN AMERICAN SOCIETY REFLECTED INANNE FLETCHER'S THE PROPOSAL MOVIE (2009): A SOCIOLOGICAL APPROACH - SEKARWULAN, WAHYU (2011)
This study is aimed to show the materialistic culture in The Proposal movie by using sociological approach. It is done by establishing two objectives: the first is analyzing the movie based on its structural elements and the second analyzing the movie based on sociological approach. This research is qualitative research. Type of data of the study is literary taken from two data sources: primary and secondary. The primary data sources are taken from The Proposal movie directed by Anne Fletcher released in 2009. while the secondary data sources are other materials taken from books, journals, and internet related to the study. Both data are collected through library research and analyzed by descriptive analysis. The study comes to the following conclusions. First, based on the structural analysis of each elements, it shows that the character and characterization, casting, plot, setting, point of view, theme, mise en scene, cinematography, sound, editing and lighting are related to each other and form the unity into good quality of a movie. Second, based on the sociological analysis, there is close relation between the movie production and the social reality underlying it, such as the materialistic culture issues that happened in American society and the different way of treatment of American citizens in public service either or other places. This movie also criticizes the power of United States immigration problem that considered as clear less.